2016
DOI: 10.5430/ijhe.v5n4p114
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the Classroom: A Pedagogical Approach to Applying Clinical Judgment by Engaging, Interacting, and Collaborating with Nursing Students

Abstract: The flipped-classroom format offers students opportunities for engagement and ownership of learning by enabling them to make sense of their views and perspectives and connect their personal and professional experiences. Student engagement and the infusion of active learning are core concepts of the educational process; given the present generation of students' exhibited preference for digital literacy, experiential learning, interactivity, and immediacy, technology is increasingly being integrated into higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 12 publications
(4 reference statements)
3
13
0
2
Order By: Relevance
“…Bergmann and Sams (2012) pointed out that the use of videos and quizzes as powerful instruments for the teachers help to share, build content, and refine practice. Similarly, in a study conducted by Tune, Sturek, and Basile (2013) as well as by Peisachovich et al (2016), FCR with frequent quizzes were found to be highly effective for better students' performance in the physiology course and in health assessment course, which was similar to our study results. But interestingly, a study conducted among the nursing students in pharmacology course by El-Banna, Whitlow, and McNelis (2017) did not demonstrate a significant difference in the academic performance of students when the FCR was applied compared to the traditional lecture-based instruction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Bergmann and Sams (2012) pointed out that the use of videos and quizzes as powerful instruments for the teachers help to share, build content, and refine practice. Similarly, in a study conducted by Tune, Sturek, and Basile (2013) as well as by Peisachovich et al (2016), FCR with frequent quizzes were found to be highly effective for better students' performance in the physiology course and in health assessment course, which was similar to our study results. But interestingly, a study conducted among the nursing students in pharmacology course by El-Banna, Whitlow, and McNelis (2017) did not demonstrate a significant difference in the academic performance of students when the FCR was applied compared to the traditional lecture-based instruction.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the study results by Peisachovich et al (2016), Chan, Lam, and Ng (2018) and Tang et al (2017), our students also have voiced out as a concern and complaint about the amount of preparation time they needed to employ this method in order to listen to the online lectures, complete the reading for in-class interactive session, and complete the assignments. They were benefited from the 1h extra preparation time provided to them in the post-cycle II, before starting the class.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Many curricula use the teaching method of flipping classrooms, and most of them have achieved optimal results (Morgan et al, 2015;Tune et al, 2013). Peisachovich et al (2016) applied classroom flipping to an undergraduate nursing program at the University of Ontario. They found that flipping the classroom helped students to learn more deeply.…”
mentioning
confidence: 99%
“…Many reported shifts in examination results (El-Banna et al, 2017;Greenwood & Mosca, 2017;Hanson, 2016;Holman & Hanson, 2016;Singla et al, 2016), employing structured surveys pre-and post-intervention with a combination of both or either open-ended questionnaires and focus groups. Descriptive statistics were used to report shifts in scores or satisfaction ratings and inductive thematic analysis used to identify emergent themes (Gilboy et al, 2015;Peisachovich et al, 2016;Saunders et al, 2017;Telford & Senior, 2017;Yacout & Shosha, 2016). Common approaches included eexperimental techniques such as quasi-experimental or randomised controlled trials (Dehghanzadeha & Jafaraghaeeb, 2018;Geist et al, 2015;Greenwood & Mosca, 2017;Holman & Hanson, 2016;Kim & Jang, 2017;Lee & Park, 2018;Maxwell & Wright, 2016;Shatto et al, 2017;Singla et al, 2016).…”
Section: Study Characteristicsmentioning
confidence: 99%